Indole Alkaloids of Leuconotis eugenifolius - Jaafar F, Mohd; A. Hadi, A.Hamid; N.H, Ismail; Awang, Khalijah (Malaysian Journal of Science, 2005)
In this study the alkaloid content of Malaysian Leuconotis eugenifolius has been carried out. From the bark of L. eugenifolius, two indole alkaloids were isolated and identified as leuconolam and E-akuammidine. The crude extract also showed positive anti-plasmodial activity. The isolation of the alkaloids is achieved by chromatographic techniques and the structural elucidations were performed via spectral methods; namely NMR, MS, IR and UV.